Dampak Penggunaan Gadget terhadap Konsentrasi Anak Usia 6-12 Tahun di Kabupaten Bogor - Felicia Irawaty; Nomi Anjelina (P3M STT Kristus Alfa Omega, 2026)
This study aims to analyze the positive and negative impacts of gadget use on the concentration of children aged 6–12 years and to examine the role of parents and Christian Religious Education teachers in guiding children. This study employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The research participants included children aged 6–12 years, parents, and Christian Religious Education teachers at an elementary school in Bogor Regency. The findings indicate that gadget use for more than three hours per day reduces children's concentration, as evidenced by difficulty maintaining focus, being easily distracted, limited social interaction, impaired physical health, and reduced perseverance in completing tasks. Nevertheless, gadgets also provide benefits as learning media when used appropriately. The researchers argue that the main problem lies not in the gadgets themselves but in the lack of supervision and limitations on their use. This study emphasizes the importance of a spiritual approach in addressing the impact of gadget use on children's concentration. The novelty of this study lies in examining the phenomenon of gadget use by highlighting the role of Christian Religious Education teachers, thereby offering a new perspective on research in child education in the digital era.